The Molecular Identification of Nephtys species (Polychaeta: Phyllodocida) from Songkhla Lake, Southern Thailand - Pattaratumrong, Manasawan Saengsakda; Wongkhamhaeng, Koraon (Naresuan University Journal: Science and Technology (NUJST); Vol 27 No 3 (2019): July-September 2019, 2019)
Polychaetes are macrobenthic fauna which play an important role in ecosystems by changing the physical nature of the seabed and nutrient cycling. They are the most dominant group in the benthic community, an important component in the food chain and bioindicators of environmental pollution. Songkhla lake has over fifty species of polychaetes and the most abundance family is Nephtyidae. Morphological identification of individual species is difficult and time-consuming, requiring expertise. This paper examined the phylogenetic relationships of the common nephtyids present in the outer sector of Songkhla Lake, Southern Thailand, Nephtys polybranchia , Nephtys oligobranchia and Nephtys sp., were studied using partial nuclear ribosomal first internal transcribed spacer (ITS1) nucleotide sequences. The results of the molecular phylogenetic analysis showed that the Nephtys can be grouped into two clades: (1) an unresolved clade including Nephtys polybranchia and Nephtys sp. as sister taxa and (2) Nephtys oligobranchia. The results indicated that ITS1 sequencing should be a useful taxonomic marker for Nephtys species in the ecological survey and routine identification. Keywords: Nephtyidae, polychaete, molecular marker, Songkhla lake, ITS1